2020
DOI: 10.1016/j.canlet.2019.10.035
|View full text |Cite
|
Sign up to set email alerts
|

PARP1 blockade is synthetically lethal in XRCC1 deficient sporadic epithelial ovarian cancers

Abstract: PARP1 inhibitor (Niraparib, Olaparib, Rucaparib) maintenance therapy improves progression-free survival in platinum sensitive sporadic epithelial ovarian cancers. However, biomarkers of response to PARPi therapy is yet to be clearly defined. XRCC1, a scaffolding protein, interacts with PARP1 during BER and SSBR. In a large clinical cohort of 525 sporadic ovarian cancers, high XRCC1 or high PARP1 protein levels was not only associated with aggressive phenotypes but was also significantly linked with poor progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 35 publications
4
29
1
Order By: Relevance
“…e Radius TM 24-well cell migration assay (Cell Biolabs, Inc., San Diego, CA, USA) was used to study cell migration and invasion [20]. To determine cell migration, we put the 0.5 mL of solution A (gel pretreatment) on every place.…”
Section: Cell Migration and Invasion Testmentioning
confidence: 99%
“…e Radius TM 24-well cell migration assay (Cell Biolabs, Inc., San Diego, CA, USA) was used to study cell migration and invasion [20]. To determine cell migration, we put the 0.5 mL of solution A (gel pretreatment) on every place.…”
Section: Cell Migration and Invasion Testmentioning
confidence: 99%
“…The balance between PARP1 and XRCC1 expression might modulate response to PARP1. Previous studies in other cancer types have reported the efficient targeting of PARP1 in XRCC1 deficient lines [ 40 , 41 , 42 ]. In our study, the most sensitive cell to PARP1 blockade, e.g., BT83, displayed PARP1 expression and concomitant absence of XRCC1 protein/mRNA expressions.…”
Section: Discussionmentioning
confidence: 99%
“…PARP-2 -deficient mouse embryonic fibroblast cells displayed a delay in DNA strand break repair similar to PARP-1 deficient cells [ 167 ]. PARP-1 blockades are synthetically lethal in XRCC1-deficient sporadic ovarian carcinoma and ductal breast carcinoma [ 168 , 169 ]. However, PARP1 and PARP2 still regulate two different yet connected aspects of DNA base damage tolerance.…”
Section: Parps In Hallmark Cancer Traitsmentioning
confidence: 99%